Kubli - Yambao, Marko A.; Rownd, Robert L. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2016)
"One silent night in a stone church by the countryside, a young priest scouts the premises after finishing his last confession. He encounters an oddly familiar figure: a wooden top, his favorite childhood toy, being spun by a little boy. As he moves closer, he drifts further from reality and into his own twisted memory. What follows is a dance between saint and sinner unraveling to a beat of guilt, secrets and shadows. The film aims to use the experimental narrative format and semiosis to play with the viewer's judgment in establishing who the oppressor and the oppressed are in the relationship and make them question how they construct their own judgments in the process."
Vita.
Undergraduate thesis
Keywords: Kubli (Short film) -- Philippines; Short films -- Philippines